The Sanctions Debate in the Work of the United Nations Since the 2000 Working Paper - Strydom, Hennie (Potchefstroom Electronic Law Journal, 2022)
In recent years the lawfulness of certain types of sanctions and the question about the usefulness of sanctions in general have become topical and widely discussed issues. Of special significance is the expanding use by powerful states of unilateral coercive measures without Security Council authorisation, or beyond Security Council authorisation, to illustrate their displeasure with the domestic or foreign policies of certain members of the international community. Over time the nature of these measures has taken on diverse forms and their encroachment on human rights and freedoms has become a matter of international concern. This contribution examines the developments that have taken place in this context since the 2000 report of the Working Group on the negative impact of sanctions by focussing on the interventions by key United Nations bodies.